Analyse des erreurs phonétiques des apprenants iraniens du FLE : le cas des groupes consonantiques /bR/ et /kR - Mohamad-Hossein Otroshi; Kamyar Abdoltajedini (Corela)
This research focuses on phonetic errors in French, in particular with the production of two clusters /bR/ and/kR/ of French as a foreign language (FFL) by 6 learners at the beginner level (A1). The aim is to analyze and explain differences in pronunciation caused by these two clusters. In so doing, the productions of 8 French words by 6 first-year French students at the University of Isfahan were recorded and analyzed. The results of this study showed that the pronunciation of these clusters is problematic, and two elements cause this: the acoustic characteristics of the components of the consonant group and the position of the group in the word. We observed five sources of the pronunciation errors of the learners: not releasing the consonant, breaking up the group, adding a vocal sound, eliding one of the group’s components, and substituting one consonant of the group with another.